Pendampingan Penyusunan Laporan Keuangan dan Digital Marketing Pada Usaha Kopi “SIDJIE” - Erin Soleha; Zulfa Zakiatul Hidayah; Indra Permana; Ahmad Rasyiddin (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
SIDJIE is a Micro, Small and Medium Enterprise (MSME) engaged in food and beverage, especially coffee drinks. This place provides various types of food and drinks. On this occasion, through community service activities carried out to help MSMEs through several programs offered and have been compiled and discussed with interested parties. Starting from debriefing and assistance in preparing financial reports and digitizing promotions was chosen as an effort to help develop these MSMEs. After this activity, it is hoped that SIDJIE will find it easier to see the financial condition of its business so that in the future it can be even better at managing its business finances. Furthermore, with the marketing digitalization program, it is hoped that it will be able to increase public knowledge of this coffee shop business and indirectly increase SIDJIE's sales.